Journal publications by pharmacy practice faculty evaluated by titution and region of the United States (2001-2003) - Craig I. Coleman (Pharmacy Practice, 2007)
Objective: To compare the quantity of manuscriptspublished in journals by departments of pharmacypractice at schools and colleges of pharmacy in theUnited States for the years 2001-2003.Methods: We utilized the Web of Sciencebibliographic database to identify publicationcitations for the years 2001 to 2003 which were thenevaluated in a number of different ways. Facultywere identified via American Association ofColleges of Pharmacy rosters for 2000-2001, 2001-2002, and 2002-2003 academic years.Results: Rankings were done based on the numberof publications per institution and average numberof publications per faculty member at an institution.Upon linear regression analysis, a relationshipexists between an institutions faculty size and thetotal number of publications but not fortenure/nontenure-track faculty ratio. Rating highestin overall publication number did not guarantee highrankings in the average number of publications perfaculty member at an institution assessment.Midwestern schools were responsible for morepublications per institution than other regions. Manyschools only generated minimal scholarship overthis evaluative period.Conclusion: While many schools have pharmacypractice faculty that strongly contributed to thebiomedical literature, other schools have not.Pharmacy practice faculty in the Midwest publishmore journal manuscripts than faculty in otherregions of the country. More pharmacy schoolsneed to engage their faculty in scholarly endeavorsby providing support and incentives.